2017
DOI: 10.9775/kvfd.2017.17748
|View full text |Cite
|
Sign up to set email alerts
|

Sıçanlarda Dimetoatla Oluşturulan Hepatotoksisite Üzerine Taflan (Laurocerasus officinalis Roem.) Meyvesinin Koruyucu Etkisi

Abstract: Citation of This ArticleEken A, Ünlü Endirlik B, Bakır E, Baldemir A, Yay AH, Cantürk F: Effect of Laurocerasus officinalis Roem. (Cherry laurel) fruit on dimethoate induced hepatotoxicity in rats. Kafkas Univ Vet Fak Derg, 23 (5): 779-787, 2017779-787, . DOI: 10.9775/kvfd.2017 Abstract Dimethoate is one of the most important organophosphate insecticides and may cause oxidative stress leading to production of free radicals and alterations in antioxidants. The aim of this study was to investigate the protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
0
1
Order By: Relevance
“…The study identified K and Mg as the main macro minerals; and, respectively, Zn and Fe as the main micro minerals in Cape gooseberry seeds, regardless of ripeness stage. K, Na, Ca, and Mg concentrations in the study were higher than some previously reported data [9,[47][48][49], inclusive that about fruit of the same origin [50], while micro mineral contents (Fe, Mn, Cu, Zn) established no such uniform trend, being either higher or close to reported data. Those differences obviously reflected the influence of fruit ripeness discussed above (published data regarded only fully ripe fruit), but value comparison also supported the assumption that the seeds were the center of mineral accumulation in Cape gooseberry fruit, as all of the studies above considered either whole fruit or fruit pulp (fruit meal) alone.…”
Section: Minerals In the Seeds Of Unripe And Underripe Cape Gooseberr...contrasting
confidence: 68%
“…The study identified K and Mg as the main macro minerals; and, respectively, Zn and Fe as the main micro minerals in Cape gooseberry seeds, regardless of ripeness stage. K, Na, Ca, and Mg concentrations in the study were higher than some previously reported data [9,[47][48][49], inclusive that about fruit of the same origin [50], while micro mineral contents (Fe, Mn, Cu, Zn) established no such uniform trend, being either higher or close to reported data. Those differences obviously reflected the influence of fruit ripeness discussed above (published data regarded only fully ripe fruit), but value comparison also supported the assumption that the seeds were the center of mineral accumulation in Cape gooseberry fruit, as all of the studies above considered either whole fruit or fruit pulp (fruit meal) alone.…”
Section: Minerals In the Seeds Of Unripe And Underripe Cape Gooseberr...contrasting
confidence: 68%